Preclinical Evaluation of Hepatoprotective Activity of Ocimum basilicum L. and Allium sativum L. - Deodelsy Bermúdez Toledo; María Boffill Cárdenas; Emoe Betancourt Morgado; Raylen Escobar Román; Ignacio Igualada Correa; Bennia Alonso Cárdenas (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Background: finding natural treatments designed to protect the liver from the damaging effects of hepatotoxins is an important topic in medical and pharmaceutical research. Objective: to pre-clinically evaluate the hepatoprotective activity of the species Ocimum basilicum L. and Allium sativum L. in an animal model of acetaminophen-induced toxicity. Methods: a preclinical pharmacological study was conducted to evaluate the hepatoprotective effect of the species Ocimum basilicum L. and Allium sativum L. against acetaminophen-induced toxicity. Adult male NMRI mice were used. They were orally administered soft extracts of the plants at doses of 200mg/kg and 400mg/kg for three consecutive days before inducing hepatotoxicity. Clinical signs of toxicity and hepatic biochemical parameters were evaluated; in addition, the morphological analysis of the liver was performed. Results: the biochemical parameters showed highly significant differences, but only three groups had results similar to the untreated control group. No macroscopic changes in the liver were confirmed. Microscopically, the absence of histopathological changes prevailed in the groups treated with Ocimum basilicum L. at both doses and Allium sativum L. at 200mg/kg; slight damage was observed by administering 400mg/kg of Allium sativum L., with significant differences from the untreated control group. Conclusions: soft extracts of the species Ocimum basilicum L. and Allium sativum L. at a dose of 200mg/kg have greater hepatoprotective activity against the toxic action of acetaminophen.